Paraphrase Practices in Academic Writing of Nursing Science Study Program, STIK Bina Husada Palembang - Agus Wahyudi; Arief Pamuji (PT FORMOSA CENDEKIA GLOBAL, 2023)
Paraphrasing has two main purposes, namely to avoid plagiarism and to make ideas easier to understand. The purpose of this research is to answer the following questions: 1. How are the paraphrasing results of the students of the Nursing Study Program STIK Bina Husada Palembang?, and 2. What are their perceptions of paraphrasing?. This research was conducted on May 27th, 2023, out of 38 students registered, only 34 students from the Nursing Science Study Program STIK Bina Husada Palembang participated in this research The students were asked to paraphrase a text containing 119 words entitled